(untitled) (Journal of Global Humanities and Social Sciences, 2023)
As the complexity of medical services and the diversity of patients’ needs increase, the doctor-patient relationship is facing unprecedented challenges. As an important part of healthcare delivery, the behavior of medical students-in-training directly affects the quality of the doctor-patient relationship and the effectiveness of healthcare delivery. However, medical students-in-training may feel confused and stressed when faced with ethical challenges and professional responsibilities. This has triggered the need for in-depth research on the professional ethics and responsibilities of medical students-in-training in the doctor-patient relationship. This paper proposes several strategies to improve the professional ethics of medical students in internship, including enhancing professional ethics education, training in communication skills, ethics training through simulation and scenario-based teaching, establishing and adhering to clinical practice guidelines, and mentoring and reflection in practice, to promote the growth of medical students in internship, improve the quality of healthcare services, and maintain a good doctor-patient relationship.